How strong is the case for the fiscal exceptionalism of the telecommunications sector?. (1st January 2012) - Cave, Martin
Telecommunications are subject to exceptional fiscal treatment in respect of both taxes and subsidies. Services are subject to special taxes in many jurisdictions; and special subsidies are paid to finance investments, especially in new fibre networks. The paper analyses the validity in general of both of these forms of treatment. In many jurisdictions the ground for collecting special taxes seems to hinge, especially in developing countries, upon the relatively low costs of tax collection. However, special taxes may discourage diffusion and restrict growth. In relation to subsidies, the justification can run from equity or industrial policy goals to the avoidance of market failure. In both instances, the argument depends on the degree to which investment in telecommunications creates externalities which enhance growth. The paper concludes that no general case for either form of special treatment has been proven.